A Cooperativa de Ensino de Mme Curie: relações entre ciência e educação em meio ao debate sobre o ensino francês entre o final do século XIX e o início do século XX - Tonetto, Sonia Regina (2014)
This work aims to analyze the ideas about methods of teaching science in the early twentieth advocated by prominent scientists as Marcellin Berthelot, Paul Langevin and Henri Poincaré and the important contribution of these scientists in the reform of French teaching, 1902. Furthermore, we sought to understand the difficulties faced in teaching in French schools of that period, we sought to also to understand what these scientists believed to be the ideal science teaching method and the influence of positivist ideas in these discussions. We analyzed in particular the role of Co-operative Education of Mme Curie (1907-1908) and the objectives of the group of teachers, including Paul Langevin, which was involved in the discussions on the reform. This work was developed from the analysis of documents filed at the Institut Curie and at Bibliothèque Nationale de France, texts and books written by scholars and scientists, with direct and indirect participation in the reform, records of lectures, articles and manuscripts of the children who participated in the cooperative, as Isabelle Chavannes and Irène Curie